Analisis Faktor yang Mempengaruhi Nilai Tukar - Harahap, Evi Syuriani; Affandi, Muhammad Rispan; Situmorang, Eduward; Sitorus P, Lampora (CV. PUSDIKRA MITRA JAYA, 2024)
This research aims to determine the influence of exports, imports, inflation and interest rates on the exchange rate. The type of research used in this research is quantitative descriptive using time series data from 2009-2023. The data sources used come from the Central Statistics Agency (BPS) and Indonesian Bank (BI) which were processed using eviews 12. The research results show that exports, inflation and interest rates have a positive and significant effect on the exchange rate while imports have a negative and significant effect on the exchange rate.